O ensino de língua portuguesa na Quarta Colônia de Imigração Italiana no RS: história e memória - Piovesan, Carolina (2021)
The current work aims to understand the teaching of Portuguese language, in the 1950s until the 1970s, in a region where signs of Italian language predominated. The motivation that leads to carry out this study is linked to the interest in producing background about the knowledge of the mother tongue — the language learned by the families — in the region of the Fourth Colony of Italian Immigration. Therefore, in this research, we propose to talk about the stories and memories of teachers who worked with the teaching and learning of the Portuguese language, in this place of Italian immigration, from Rio Grande do Sul. For that, it is necessary to know about the history of Italian immigration in Brazilian territory and about the constitution of Portuguese language teaching in Brazil. The theoretical perspective that underlies the research refers to the History of Linguistic Ideas (HIL) related to Discourse Analysis (AD) of French line. Thus, when considering the discursive practices of teachers, we are building meanings that represent the social, historical and ideological positions of these subjects who teach the language. To carry out the study, we sought to analyze recordings of interviews with literacy teachers, contained in a database under construction, during the mentioned period. Thus, based on the theoretical device of Discourse Analysis, we investigate our object of study, the teachers' discourse, and mobilize the different analytical devices, which are constituted throughout the analysis.